IMPLEMENTATION OF DIAGNOSTIC ASSESSMENT IN GRADE VI TEACHING AT THE RIGHT LEVEL APPROACH IN INDONESIAN LANGUAGE LESSONS IN ELEMENTARY SCHOOL - Asharif Suleman, Muh.; Idayanti, Zulfi (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2024)
This study aims to examine why teachers need to use diagnostic assessments of Indonesian language lessons in classes that implement the Teaching at the Right Level (TARL) approach. This study is a qualitative study with a case study approach. This study was conducted in class V (NUH) with 47 students. Data were obtained by collecting the results of diagnostic assessments of three different classes (up to medium, low) of Indonesian language lessons. The assessment was adapted from the book